Geotechnical frontiers 2017. selected papers from sessions of Geotechnical Frontiers 2017, March 12-15, 2017, Orlando, Florida - Brandon, Thomas L.; Valentine, Richard J. (GSP (Series), 2017)
GSP 276 contains 60 peer-reviewed papers on waste containment and sustainable geoengineering presented at Geotechnical Frontiers 2017, held in Orlando, Florida, March 12-15, 2017.